All-Optical Polarization Manipulation Through Orbital Polarization Holography - Lyu, Ziyao; Wang, Changshun (Frontiers in Physics, 2022)
Spin-orbital optical phenomena are closely related with light-matter interactions and have been of great interest in the last few years. Here, the effect of optical orbital angular momentum (OAM) on polarized waves carrying spin angular momentum (SAM) has been investigated experimentally by means of orbital polarization holography and analyzed with Jones matrices theoretically. We report that all-optical OAM-to-polarization manipulation can be realized with a controllable holographic grating recorded through the interference of orthogonally polarized beams in various helical modes in a kind of photo-alignment supermolecular liquid-crystalline films. The polarization states of diffraction beams can be controlled through adjusting the spatial degree of freedom of the recording light field. The OAM-controlled polarization manipulation is discussed in terms of Jones matrices and photoinduced birefringence. Because of the realization of OAM-to-SAM conversion, this work may find applications in a variety of devices.